Thank you for the opportunity to help you with your question! Hope your day is going well!

The goal is to get y alone.

1. 6x-9y=3 (divide by 3 to the whole equation)

2x-3y=1 (subtract 2x from both sides)

-3y=-2x+1 (divide by -3 to the whole equation)

y=2/3x-1/3

Just use random x values, to find some y values

x

y

0

-1/3

1

1/3

2

1

(0,-1/3)(1,1/3)(2,1)

2. x+3y=0 (subtract x from both sides)

3y=-x (divide by three to both sides)

y=-x/3

x

y

0

0

1

-1/3

2

-2/3

(0,0),(1,-1/3) (2,-2/3)

Note there are a ton more points, you just keep using different x values to find more points.

Please let me know if you need any clarification. I'm always happy to answer your questions. Leave a positive review if you are happy!

Sep 11th, 2015

I realized I have been doing the wrong things for these problems. I will fix each of these (I forgot to read the title, and it clearly says use substitution method).

So for this problem, solve the second equation for x and substitute in what you find for x into the second equation.

x+3y=0

x=-3y

6(-3y)-9y=3

-18y-9y=3

-27y=3 (divide by negative 27 to both sides)

y=-3/27=-1/9

Hence y=-1/9

Substitute y=-1/9 into x=-3y to solve for x

x=-3(-1/9)

x=1/3

Therefore the answer is x=1/3 and y=-1/9

Sep 11th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.